MODEL OF PROVIDING LIFE QUALITY AND SAFETY OF NUTRITION IN EDUCATIONAL ENVIRONMENT - Korbukova , Nelya; Krylova , Larisa; Afanasyeva , Galina; Tarasova , Veronika; Tokareva , Tatiana; Tarasov , Alexander; Karelina , Natalia (Revista Inclusiones, 2020)
The urgency of the problem under study is conditioned by the lower level of population’s food security and quality during continuous education, as well as by the importance of the conscious choice of nutritious food, which implies the consumption of enough quantity of proteins, fats, carbohydrates, vitamins, macro- and microelements for normal functioning of an organism in general. The aim of the paper is to elaborate recommendations on creating conditions that that would provide students undergoing continuous education with knowledge on high-quality and safe nutrition, food ration, regular access to physical education and popular sport, leading a healthy lifestyle. The leading method was a pedagogical experiment that could help to reveal the facts of poor and unbalanced day-time nutrition among students. The state of students’ health during the study period has been monitored and evaluated. The nutrition priorities of modern youth, their conscious choice of foods and life style are examined. The main results of the work was the model of the food safety in continuous education developed by the authors.